2006
DOI: 10.1038/sj.onc.1210046
|View full text |Cite
|
Sign up to set email alerts
|

ALK5 promotes tumor angiogenesis by upregulating matrix metalloproteinase-9 in tumor cells

Abstract: Transforming growth factor beta 1 (TGF-b1) is a potent tumor suppressor but, paradoxically, TGF-b1 enhances tumor growth and metastasis in the late stages of cancer progression. This study investigated the role of TGF-b type I receptor, ALK5, and three mitogen-activated protein kinases (MAPKs) in metastasis by breast cancer cell line MDA-MB-231. We show that autocrine TGF-b signaling in MDA-MB-231 cells is required for tumor cell invasion and tumor angiogenesis. Expression of kinaseinactive ALK5 reduces tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(129 citation statements)
references
References 63 publications
8
116
1
2
Order By: Relevance
“…In extension to previous analyses, our results furthermore indicate that the microRNAmodulated role of TGFb signaling in directing EMT/ MET and invasion of ATCs also involves the control of TGFBR1 expression by the miR-200 family. These results are supported by previous analyses in other tumors and tumor-derived cells, in which it was shown that TGFBR1 acting through SMAD2/SMAD3 promotes metastasis and angiogenesis by modulating gene expression, for instance, the upregulation of metalloproteinase-9 and/or vascular endothelial growth factor (Cui et al, 1996;Piek et al, 1999;Guzinska-Ustymowicz and Kemona, 2005;Safina et al, 2007;Shao et al, 2009). Notably, recent evidence indicates that altered TGFb signaling also modulates microRNA maturation by RSMADs, as shown for the proinvasive miR-21 (Davis et al, 2008).…”
Section: Downregulation Of Micrornassupporting
confidence: 75%
“…In extension to previous analyses, our results furthermore indicate that the microRNAmodulated role of TGFb signaling in directing EMT/ MET and invasion of ATCs also involves the control of TGFBR1 expression by the miR-200 family. These results are supported by previous analyses in other tumors and tumor-derived cells, in which it was shown that TGFBR1 acting through SMAD2/SMAD3 promotes metastasis and angiogenesis by modulating gene expression, for instance, the upregulation of metalloproteinase-9 and/or vascular endothelial growth factor (Cui et al, 1996;Piek et al, 1999;Guzinska-Ustymowicz and Kemona, 2005;Safina et al, 2007;Shao et al, 2009). Notably, recent evidence indicates that altered TGFb signaling also modulates microRNA maturation by RSMADs, as shown for the proinvasive miR-21 (Davis et al, 2008).…”
Section: Downregulation Of Micrornassupporting
confidence: 75%
“…MMP-9 contributes to tumor angiogenesis by promoting recruitment of endothelial cells (Bergers et al, 2000) and pericytes (Chantrain et al, 2004). Indeed, TGF-b1-mediated tumor angiogenesis is significantly reduced when MMP-9 is suppressed by RNA interference (short interfering RNA, siRNA) (Safina et al, 2007). The molecular mechanism of MMP-9 regulation by TGF-b1 is still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies with kinase inhibitors have implicated p38MAPK in MMP-9 regulation by TGF-b1 in breast cancer cells (Farina et al, 1998;Suarez-Cuervo et al, 2004). Recent studies with dominant-negative (dn) mutants of MAPKs have shown that p38MAPK is dispensable, whereas MEK-ERK contributes to TGF-b1 regulation of MMP-9 (Safina et al, 2007). Ras-ERK signaling has been also implicated in regulation of MMP-9 in fibroblasts and epithelial cell lines (Gum et al, 1996;Himelstein et al, 1997;Iyer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAK1 was proved to be a critical regulator of matrix-metalloproteinase-9 (MMP-9) expression (Safina et al, 2008). MMP-9/gelatinase-B contributes to the invasive and metastatic potential of cancer cells (Farina et al, 1998;Suarez et al, 2004;Safina et al, 2007), as well as to tumor angiogenesis, by promoting recruitment of endothelial cells (Bergers et al, 2000) and pericytes (Chantrain et al, 2004).…”
Section: Discussionmentioning
confidence: 99%